Wastewater-based epidemiology of norovirus in Israel, 2022 - Tal Maoz Atias; Yaniv Lustig; Enosh Tomer; Oran Erster; Noam Barda; Neta S. Zuckerman; Itay Bar-Or (Science of The Total Environment, 2026)

Multiple African-origin circulating poliovirus-2 emergences identified in Israel: A reminder of an ongoing global challenge - Neta S. Zuckerman; Hagar Eliyahu; Yaniv Lustig; Danit Sofer; Lester M. Shulman; Leah Weiss; Rinat Vasserman; Reut Gabai; Keren Friedman; Tatyana Kushnir; Lihi Gershon; Ira Aguvaev; et al. (Science of The Total Environment, 2025)

Newly designed amplicons-based method for near-full-length genome (NFLG) sequencing of HIV-1 group M recombinant forms - Roy Moscona; Tali Wagner; Miranda Geva; Efrat Bucris; Oran Erster; Neta S. Zuckerman; Orna Mor (Molecular Biology Reports, 2025)
Background Over the years the spread of HIV-1 across the globe resulted in the creation of multiple subtypes and new recombinant forms (RFs). While the pol gene region of the HIV-1 genome is used for resistance mutations analysis and initial detection of RFs, whole genome sequencing analysis is required to determine recombination events across the viral genome. Here, we present a newly designed robust near-full length genome (NFLG) sequencing approach for the sequencing of HIV-1 genomes, out of clinical whole blood samples. This method has been successfully tested for various HIV-1 subtypes and RFs. Methods and results The method is based on an in-house developed set of 32 pan-genotypic primer pairs, divided into two pools, each containing 16 primer pairs covering the entire HIV-1 genome. Two parallel multiplex PCR reactions were used to generate 32 overlapping DNA fragments spanning the HIV-1 genome. Nextera XT protocol was used to obtain barcoded DNA libraries, which were sequenced with the Illumina Miseq platform using a V3 kit. A consensus sequence was determined for each sample and was used to define recombination events across the genome. For this aim, a combined analysis of several computational tools including HIV BLAST, phylogenetic analysis, RIP, SimPlot + + and jpHMM were employed. Overall, plasma samples from 33 patients suspected to carry RFs and 2 different, known pure subtypes controls, were included in this study. Genome coverage varied between RFs, while the gag and pol genes were nearly fully covered, the highly variable env gene region was not. Yet, these NFLG analyses enabled the identification of recombination events genome wide. Conclusions In summary, we describe a methodology for HIV-1 NFLG sequencing, which is based on partially overlapping, multiple PCR fragments, spanning the HIV-1 genome. Additionally, this newly refined method was compared to HIV-1 NFLG results of PCR-free metagenomic sequencing and proved to obtain greater coverage of the HXB2 reference genome. Yet, further testing and validation on a larger cohort is required. Still, this method enables sequencing of 20 different patient samples in a single MiSeq sequencing run and was used for the characterization of different HIV-1 RFs and pure subtypes circulating in Israel.

Exploring hepatitis A dynamics in Israel, 2019–2022 - Yael Gozlan; Neta S. Zuckerman; Mayyan Yizchaki; Rivka Rich; Itay Bar-Or; Orna Mor (Science of The Total Environment, 2024)

Incursion of SARS-CoV-2 BA.2.86.1 variant into Israel: National-scale wastewater surveillance using a novel quantitative real-time PCR assay - Oran Erster; Itay Bar-Or; Roberto Azar; Hadar Assraf; Areej Kabat; Batya Mannasse; Vardit Moshayoff; Shay Fleishon; Sharon Alroy Preis; Ruth Yishai; Noa Teijman-Yarden; Irina Aguvaev; et al. (Science of The Total Environment, 2024)

Environmental surveillance detected type 3 vaccine-derived polioviruses in increasing frequency at multiple sites prior to detection of a poliomyelitis case - Merav Weil; Danit Sofer; Lester M. Shulman; Leah Weiss; Nofar Levi; Irina Aguvaev; Zvi Cohen; Klil Kestin; Rinat Vasserman; Michal Elul; Ilana S. Fratty; Neta S. Zuckerman; et al. (Science of The Total Environment, 2023)

JC virus identified in a patient with persistent and severe West Nile virus disease - Neta S. Zuckerman; Victoria Indenbaum; Ron Milo; Ella Mendelson; Yaniv Lustig (Journal of NeuroVirology, 2019)